Digital equity in a crowded tool space: Navigating opportunities and challenges for equitable implementation of conservation technologies - Karyn M. Tabor; Natasha Stavros; Dawn Biehler; Liliana C. Castillo‐Villamor; Dillon Mahmoudi; Luis Mario Moreno Amado; Margaret B. Holland (Conservation Science and Practice)
Abstract We call on conservation funders, technology developers, and practitioners to explore how digital technologies can transform conservation practice. Actors supporting, developing, and funding digital technologies for conservation must address digital inequity and reduce the societal risks of digital technologies that may undermine conservation goals. We highlight the challenges in leveraging digital conservation technologies and recommend approaches to increase access to digital technologies for uptake by diverse users while supporting equitable participation from diverse user communities to shape digital technologies and their applications. Improving access to and use of tools may be achieved through strategic funding for digital design that recognizes and supports local solutions and diverse practices and perspectives. With increasing digital access, funders must also emphasize adherence to safeguards and protocols to reduce risks associated with digital technologies. By adopting more ethical methodologies related to digital technologies, we not only enhance global sustainability but also foster collaborative relationships with communities, recognizing the intrinsic value of their expertise in conservation initiatives and jointly safeguarding the environment to ensure the well‐being of all. Encouraging more equitable approaches to conservation technologies underpins global priorities for sustainable development by centering and supporting the communities most directly involved in conservation action.